NEW ZEALAND FORMULARY FOR CHILDREN–A CASE STUDY OF NATIONAL PAEDIATRIC FORMULARY DEVELOPMENT. Issue 1 (14th December 2015) - Simpson, Bryan; Reith, David; Medlicott, Natalie; Smith, Alesha; Tilyard, Murray
Abstract : Background: The New Zealand Formulary for Children (NZFc) was developed to build on the New Zealand Universal List of Medicines through the addition of clinical information about medicines use in paediatrics. The structure and content of the NZFc is based on the British National Formulary for Children (BNFc) but is adapted for New Zealand practice. Aims: To adapt the BNFc to provide New Zealand healthcare professionals with information about the selection, prescribing, dispensing, and administration of medicines; to link the clinical information with subsidy and registration status of medicines; to incorporate additional resources according to local requirements. Methods: The initial release (November, 2013) of the NZFc was adapted from the latest version of the BNFc focusing on relevance to NZ practice. The BNFc prescribing notes were reviewed by medical specialists and clinical pharmacists before review and approval by an editorial advisory board. The BNFc drug monographs were compared to New Zealand approved Medicine Datasheets (NZAMD) and tailored to reflect New Zealand approved indications and doses. The NZFc is an on-line publication provided as open access within New Zealand. When off-label uses were identified, validation was undertaken using appropriate alternate resources. Results: The NZFc was successfully developed and user statistics indicate that it is being utilised by the New Zealand health sector with 172796 visitors (February 2015). Also, monthly page views have steadily increased from 35944 (November 2013) to 216064 (February 2105). Conclusion: The project demonstrated that it is possible to adapt the BNFc for application in other countries.